PENGELOLAAN PEMBELAJARAN MATEMATIKA KONTEKSTUAL DI SEKOLAH MENENGAH KEJURUAN - Sri Budiyati; Sutama Sutama; Sabar Narimo (Universitas Pekalongan, 2013)
The research objective is to describe contextual-based math learning management, which includes planning, implementation and evaluation as well as describe the constraints of experienced math teachers in the implementation of contextual-based mathematics learning at SMK Negeri 3 Klaten. The research method used is descriptive qualitative research, research data on the implementation of contextual learning was collected using interviews, observation and documentation. It is concluded in conclusion: (1) Planning learning early in the learning of mathematics held by preparing syllabi and lesson plans, (2) implementation of contextual learning mathematics in SMK Negeri 3 Klaten is not optimal, (3) Ratings are not only assess the final outcome but also to assess the process. Implementation of learning mathematics is not optimal constrained by: (1) Teachers do not fully understand and master the contextual learning, (2) Teachers difficulties when learning material linked with the life situation that is already known by the student, (3) Teachers still tend to use the lecture method, although teachers have learned a variety of learning methods.